Investigation of Air Exergy from Condenser of Air Split-Conditioner Heat Pump and Its Exergetic Efficiency Depending on Outside Air Temperature - Volodymyr Labay; Hanna Klymenko; Mykola Gensetskyi (Energy Engineering and Control Systems)
Rising prices for fuel and energy resources make the problem of using alternative energy sources and energy saving relevant not only for the economy of Ukraine, but also for the world economy. One of the ways to reduce energy consumption is the use of air split-conditioner heat pumps in building heating systems, which are using up to 1 kW of electricity from the grid to transport up to 5 kW of heat energy from the outdoor air to the indoor air. The energy perfection of air split-conditioner heat pumps can best be established only on the basis of the analysis of their exergy efficiency. And this allowed substantiating the relevance of such a study, which made it possible to establish the exergy of air from the condenser of the heat pump air split-conditioner and its exergetic efficiency. The author’s innovative mathematical model for the analysis of operation of single-stage freon heat pumps of air split-conditioners by exergetic method is used in this article. The exergy of the air from the condenser of the air split-conditioner heat pump by Mitsubishi Electric and its exergetic efficiency with the standard heat capacity of 3200 W with R32 refrigerant depending on the outside air temperature have been established.